2021
DOI: 10.1038/s41598-021-90908-x
|View full text |Cite
|
Sign up to set email alerts
|

The blood oxygen level dependent (BOLD) effect of in-vitro myoglobin and hemoglobin

Abstract: The presence of deoxygenated hemoglobin (Hb) results in a drop in T2 and T2* in magnetic resonance imaging (MRI), known as the blood oxygenation level-dependent (BOLD-)effect. The purpose of this study was to investigate if deoxygenated myoglobin (Mb) exerts a BOLD-like effect. Equine Met-Mb powder was dissolved and converted to oxygenated Mb. T1, T2, T2*-maps and BOLD-bSSFP images at 3Tesla were used to scan 22 Mb samples and 12 Hb samples at room air, deoxygenation, reoxygenation and after chemical reduction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 41 publications
1
12
0
Order By: Relevance
“…Currently, these intriguing pathophysiologic responses are still not fully understood. Furthermore, recent research by Guensch et al has shown that myoglobin (Mb) desaturation may also play into the measured signal, although Mb desaturates later than Hb [25]. However, even a compound measure of Hb and Mb desaturation may be of importance in the characterization of PAOD as suggested by our results.…”
Section: Discussionsupporting
confidence: 60%
“…Currently, these intriguing pathophysiologic responses are still not fully understood. Furthermore, recent research by Guensch et al has shown that myoglobin (Mb) desaturation may also play into the measured signal, although Mb desaturates later than Hb [25]. However, even a compound measure of Hb and Mb desaturation may be of importance in the characterization of PAOD as suggested by our results.…”
Section: Discussionsupporting
confidence: 60%
“…This may contribute to myocardial injury after non-cardiac surgery (MINS) ( 4 ), which has been increasingly focused on over the recent years. Techniques such as oxygenation-sensitive cardiovascular magnetic resonance (OS-CMR) can non-invasively interrogate changes in myocardial oxygenation on a tissue level with high spatial resolution based on local deoxyhemoglobin fractions ( 5 , 6 ). In 2019, we reported that left ventricular myocardial oxygenation measured by OS-CMR had a curvi-linear association with mean arterial pressure ( 7 ).…”
Section: Introductionmentioning
confidence: 99%
“…6 OS-CMR exploits the signal attenuating effects of the local deoxyhemoglobin fraction as an endogenous contrast, primarily in the compartment of post-capillary myocardial venules. 6,7 A breathing maneuver consisting of a period of hyperventilation followed by a long voluntary breath-hold, triggers a vasoactive response with a myocardial oxygenation surplus. 8 An impaired response, shown by a blunted increase or even signal reduction below baseline, was shown to reflect coronary vascular dysfunction.…”
mentioning
confidence: 99%